1987
DOI: 10.1111/j.1530-0277.1987.tb01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Diagnosis of Depression in Alcoholics

Abstract: We examined depressive symptoms, using the Beck Depression Inventory (BDI), in a group of 50 alcoholic patients, diagnosed according to DSM III criteria during active drinking, withdrawal (4 days after their last drink), and abstinence (24 days after their last drink). DSM III diagnoses of major depression were made in 16 (32%) of the patients. The diagnoses were made using the NIMH Diagnostic Interview Schedule (DIS) between the 10th and 24th day after the patients' last drink. Depressive symptoms decreased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…Limits of severity are based on mean scores (i.e., normal range below 50, mild to minimal depression 50-59, moderate to marked depression 60-69, severe to extreme depression 70 and over). BDI has been used widely in research studies that have investigated individual differences in severity of levels of depression (Dorus, Kennedy, Gibbons, & Ravi, 1987;Hengeveld, Ancion, & Rooifmans, 1987;Steer, Beck, & Shaw, 1985;Steer, McElroy, & Beck, 1993).…”
Section: Dependent Measuresmentioning
confidence: 99%
“…Limits of severity are based on mean scores (i.e., normal range below 50, mild to minimal depression 50-59, moderate to marked depression 60-69, severe to extreme depression 70 and over). BDI has been used widely in research studies that have investigated individual differences in severity of levels of depression (Dorus, Kennedy, Gibbons, & Ravi, 1987;Hengeveld, Ancion, & Rooifmans, 1987;Steer, Beck, & Shaw, 1985;Steer, McElroy, & Beck, 1993).…”
Section: Dependent Measuresmentioning
confidence: 99%
“…Among the psychological states observed in recently sober alcoholic patients, depressed mood is most prominent [1], The majority of such patients appear to suffer from secondary self-limited affective syndromes rather than from enduring primary affective disorders [2], For instance, Dorus et al [3] found that 67% of male alcoholics were depressed on admission for treatment, as measured by the Beck Depression Inventory (BDI), but that this proportion dropped to 18% by day 24 without antidepressant therapy. Clinical ex perience suggests that the acute depression experienced by these patients is an adaptive response to situational stressors.…”
mentioning
confidence: 99%
“…They identifi ed important methodological confounds in the published studies: a failure to distinguish primary from secondary depression, the confl ation of symptoms related to withdrawal with those of enduring disorders, and lack of attention to family history of depression as a potential moderator of treatment response. Dorus et al (1987) later reported that, although depressive symptoms commonly occur during withdrawal, they often improve spontaneously with abstinence from alcohol, which was supported by the fi ndings of Brown and Schuckit (1988). Subsequently, there were many studies of antidepressants (both tricyclic antidepressants and selective serotonin reuptake inhibitors [SSRIs]) to treat depression in alcoholic patients.…”
Section: Medications To Treat Comorbid Psychiatric Disorders and Redumentioning
confidence: 73%